A Link Between Methylglyoxal and Heart Failure During HIV-1 Infection - Dash, Prasanta K.; Alomar, Fadhel A.; Cox, Jesse L.; McMillan, JoEllyn; Hackfort, Bryan T.; Makarov, Edward; Morsey, Brenda; Fox, Howard S.; Gendelman, Howard E.; Gorantla, Santhi; Bidasee, Keshore R. (Frontiers in Cardiovascular Medicine, 2021)
Early-onset heart failure (HF) continues to be a major cause of morbidity and mortality in people living with human immunodeficiency virus type one (HIV-1) infection (PLWH), yet the molecular cause(s) remain poorly defined. Herein NOD.Cg-PrkdcscidIl2rgtm1Wjl/SzJ humanized mice (Hu-mice), plasma from PLWH, and autopsied cardiac tissues from deceased HIV seropositive individuals were used to assess if there is a link between the glycolysis byproduct methylglyoxal (MG) and HF in the setting of HIV-1 infection. At five weeks post HIV infection, Hu-mice developed grade III-IV diastolic dysfunction (DD) with an associated two-fold increase in plasma MG. At sixteen weeks of infection, cardiac ejection fraction and fractional shortening also declined by 26 and 35%, and plasma MG increased to four-fold higher than uninfected controls. Histopathological and biochemical analyses of cardiac tissues from Hu-mice 17 weeks post-infection affirmed MG increase with a concomitant decrease in expression of the MG-degrading enzyme glyoxalase-1 (Glo1). The endothelial cell marker CD31 was found to be lower, and coronary microvascular leakage and myocardial fibrosis were prominent. Increasing expression of Glo1 in Hu-mice five weeks post-infection using a single dose of an engineered AAV2/9 (1.7×1012 virion particles/kg), attenuated the increases in plasma and cardiac MG levels. Increasing Glo1 also blunted microvascular leakage, fibrosis, and HF seen at sixteen weeks post-infection, without changes in plasma viral loads. In plasma from virally suppressed PLWH, MG was also 3.7-fold higher. In autopsied cardiac tissues from seropositive, HIV individuals with low viral log, MG was 4.2-fold higher and Glo1 was 50% lower compared to uninfected controls. These data show for the first time a causal link between accumulation of MG and HF in the setting of HIV infection.